2013
DOI: 10.1540/jsmr.49.89
|View full text |Cite
|
Sign up to set email alerts
|

Blebbistatin, a myosin II inhibitor, suppresses Ca<sup>2+</sup>-induced and “sensitized”-contraction of skinned tracheal muscles from guinea pig

Abstract: Blebbistatin, a potent inhibitor of myosin II, has inhibiting effects on Ca2+-induced contraction and contractile filament organization without affecting the Ca2+-sensitivity to the force and phosphorylation level of myosin regulatory light chain (MLC20) in skinned (cell membrane permeabilized) taenia cecum from the guinea pig (Watanabe et al., Am J Physiol Cell Physiol. 2010; 298: C1118–26). In the present study, we investigated blebbistatin effects on the contractile force of skinned tracheal muscle, in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In smooth muscle, we previously found that blebbistatin suppressed the force development independent of Ca 2+ sensitivity for the force and MLC phosphorylation level in β escin skinned taenia cecum (7) and trachea (8), and conformational changes in SMM (7), and these results indicates direct inhibition of actin-myosin interaction through modulation of SMM ATPase activity and/or SMM structure by blebbistatin. Therefore, the present result that blebbistatin had little effects on detachment of fast cycling crossbridge (τfast-detach in Table 2) supports our previous conclusion (7,8), since the detachment of the fast cycling crossbridge depends on the dephosphorylation of MLC (13,Formula 3), and also the previous evidence that blebbistatin might not act after phosphate release from SMM (1, 2).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In smooth muscle, we previously found that blebbistatin suppressed the force development independent of Ca 2+ sensitivity for the force and MLC phosphorylation level in β escin skinned taenia cecum (7) and trachea (8), and conformational changes in SMM (7), and these results indicates direct inhibition of actin-myosin interaction through modulation of SMM ATPase activity and/or SMM structure by blebbistatin. Therefore, the present result that blebbistatin had little effects on detachment of fast cycling crossbridge (τfast-detach in Table 2) supports our previous conclusion (7,8), since the detachment of the fast cycling crossbridge depends on the dephosphorylation of MLC (13,Formula 3), and also the previous evidence that blebbistatin might not act after phosphate release from SMM (1, 2).…”
Section: Discussionmentioning
confidence: 82%
“…Also, blebbistatin at around 10 μM inhibited the contraction of intact smooth muscle preparations and smooth muscle cell (3)(4)(5)(6). Furthermore, we reported that blebbistatin inhibited the contraction of skinned (cell membrane permeabilized) taenia cecum (7) and trachea (8) from the guinea pig without affecting the phosphorylation level of myosin light chain (MLC).…”
Section: Introductionmentioning
confidence: 92%